(untitled) (Research, Society and Development, 2021)
The study of personal strengths is one of the constructs of positive psychology and its foundations can be used as tools for the improvement of teaching practice. Therefore, this study sought to investigate, from the teachers’ point of view, which character forces are considered important for their professional practice. This is an exploratory study with a quantitative approach. 82 teachers from a public educational institution who taught at different levels of education participated, in northeastern Brazil, 61% were female, 41.5% had an average of 30 students per class. As a data collection instrument, we used a questionnaire with personal, professional and health characteristics and a question: about character strengths, which do you consider the most important for the exercise of teaching?. Data were collected using an electronic form, google form ®. Data analysis was performed using SPSS software, version 21. The results revealed that, for teachers, the most important character forces for teaching are: social intelligence, citizenship, love for learning, creativity, love, integrity, mind open, hope, persistence, curiosity, equity, humility and leadership. There were significant associations between the importance of social intelligence and sex, as well as between the importance of exercising citizenship and the average number of students per class. There was a greater emphasis on the human nature of the teaching and learning process.